Chromosome 17p Homodisomy Is Associated With Better Outcome in 1p19q Non‐Codeleted and IDH‐Mutated Gliomas. (8th July 2016) - Labussière, Marianne; Rahimian, Amithys; Giry, Marine; Boisselier, Blandine; Schmitt, Yohann; Polivka, Marc; Mokhtari, Karima; Delattre, Jean‐Yves; Idbaih, Ahmed; Labreche, Karim; Alentorn, Agusti; Sanson, Marc
Abstract : Background: The 1p19q non‐codeleted gliomas with IDH mutation, defined as "molecular astrocytomas, " display frequent TP53 mutations and have an intermediate prognosis. We investigated the prognostic impact of copy number‐neutral loss of heterozygosity (CNLOH) in 17p in this population. Methods: We analyzed 793 gliomas (206 grade II, 377 grade III, and 210 grade IV) by single nucleotide polymorphism array and for TP53 mutations. Results: Homodisomy revealed by CNLOH was observed in 156 cases (19.7%). It was more frequent in astrocytomas and oligoastrocytomas (98/256, 38%) than oligodendrogliomas (28/327, 8.6%; p < .0001) or glioblastoma multiforme (30/210, 14.3%; p < .0001), tightly associated with TP53 mutation (69/71 vs. 20/79; p = 2 × 10 −16 ), and mutually exclusive with 1p19q codeletion (1/156 vs. 249/556; p < .0001). In the group of IDH ‐mutated 1p19q non‐codeleted gliomas, CNLOH 17p was associated with longer survival (86.3 vs. 46.2 months; p = .004), particularly in grade III gliomas (overall survival >100 vs. 37.9 months; p = .007). These data were confirmed in an independent dataset from the Cancer Genome Atlas. Conclusion: CNLOH 17p is a prognostic marker and further refines the molecular classification of gliomas. Implications for Practice: Homodisomy of chromosome 17p (CNLOH 17p) is a frequent feature in IDH ‐mutated 1p19q non‐codeleted gliomas (group 2). It is constantly associated with TP53 mutation. It was found, within this specific molecular group of gliomas (corresponding to molecular astrocytomas), that CNLOH 17p is associated with a much better outcome and may therefore represent an additional prognostic marker to refine the prognostic classification of gliomas. Abstract : Seven hundred ninety‐three gliomas (grades II–IV) were analyzed by single nucleotide polymorphism array and for TP53 mutations. Homodisomy revealed by copy number‐neutral loss of heterozygosity (CNLOH) was observed in 156 cases (19.7%), was tightly associated with TP53 mutation, and was mutually exclusive with 1p19q codeletion. In IDH ‐mutated 1p19q non‐codeleted gliomas, CNLOH 17p was associated with longer survival (86.3 vs. 46.2 months), particularly in grade III gliomas (>100 vs. 37.9 months).